Pharmacokinetics and Safety of Omadacycline in Subjects with Impaired Renal Function - Berg, Jolene K.; Tzanis, Evan; Garrity-Ryan, Lynne; Bai, Stephen; Chitra, Surya; Manley, Amy; Villano, Stephen (Antimicrobial agents and chemotherapy, 2018)
Many antibiotics require dose adjustments in patients with renal impairment and/or in those undergoing hemodialysis. Omadacycline, the first aminomethylcycline antibiotic in late-stage clinical development, displays activity against a broad spectrum of bacterial pathogens, including drug-resistant strains. Data from completed phase 3 studies of omadacycline for the treatment of acute bacterial skin and skin structure infections (ABSSSI) and community-acquired bacterial pneumonia (CABP) showed intravenous (i.v.) to once-daily oral omadacycline to be clinically effective and well tolerated. To determine if the dosing of omadacycline should be adjusted in patients with impaired renal function, a phase 1 study examining the pharmacokinetics (PK) and safety of i.v. omadacycline (100 mg) was conducted in subjects with end-stage renal disease (ESRD) on stable hemodialysis ( n = 8) and in matched healthy subjects ( n = 8). i.v. administration of omadacycline produced similar plasma concentration-time profiles in subjects with ESRD and healthy subjects. Further, in subjects with ESRD, similar values of the PK parameters were observed when omadacycline was administered i.v. after or before dialysis. The mean area under the concentration-time curve from time zero extrapolated to infinity in plasma was 10.30 μg · h/ml when omadacycline was administered to ESRD subjects after dialysis, 10.20 μg · h/ml when omadacycline was administered to ESRD subjects before dialysis, and 9.76 μg · h/ml when omadacycline was administered to healthy subjects. The mean maximum observed concentration of omadacycline in plasma in ESRD subjects was 1.88 μg/ml when it was administered after dialysis and 2.33 μg/ml when it was administered before dialysis, and in healthy subjects it was 1.92 μg/ml. The 100-mg i.v. dose of omadacycline was generally safe and well tolerated in both ESRD and healthy subjects. This study demonstrates that no dose adjustment is necessary for omadacycline in patients with impaired renal function or on days when patients are receiving hemodialysis.